Causative variants linked with limb girdle muscular dystrophy in an Iranian population: 6 novel variants. Issue 2 (14th November 2022) - Mianesaz, Hamidreza; Ghalamkari, Safoura; Salehi, Mansoor; Behnam, Mahdiyeh; Hosseinzadeh, Majid; Basiri, Keivan; Ghasemi, Majid; Sedghi, Maryam; Ansari, Behnaz
Abstract: Background: Limb‐girdle muscular dystrophy (LGMD) is a non‐syndromic muscular dystrophy caused by variations in the genes involved in muscle structure, function and repair. The heterogeneity in the severity, progression, age of onset, and causative genes makes next‐generation sequencing (NGS) a necessary approach for the proper diagnosis of LGMD. Methods: In this article, 26 Iranian patients with LGMD criteria were diagnosed with disease variants in the genes encoding calpain3, dysferlin, sarcoglycans and Laminin α‐2. Patients were referred to the hospital with variable distribution of muscle wasting and progressive weakness in the body. The symptoms along with biochemical and EMG tests were suggestive of LGMD; thus the genomic DNA of patients were investigated by whole‐exome sequencing including flanking intronic regions. The target genes were explored for the disease‐causing variants. Moreover, the consequence of the amino acid alterations on proteins' secondary structure and function was investigated for a better understanding of the pathogenicity of variants. Variants were sorted based on the genomic region, type and clinical significance. Results: In a comprehensive investigation of previous clinical records, 6 variations were determined as novel, including c.1354–2 A > T and c.3169_3172dupCGGC in DYSF, c.568 G > T in SGCD, c.7243 C > T, c.8662_8663 insT and c. 4397G > C in LAMA2 . Some of the detected variants were located in functional domains and/or near to the post‐translational modification sites, altering or removing highly conserved regions of amino acid sequence. Abstract : Causative variants linked with LGMD in an Iranian population.